Funny Current and Cardiac Rhythm: Insights from HCN Knockout and Transgenic Mouse Models - Baruscotti, Mirko; Bucchi, Annalisa; Barbuti, Andrea; DiFrancesco, Dario (Frontiers in Physiology, 2012)
In the adult animal the sinoatrial node (SAN) rhythmically generates a depolarizing wave that propagates to the rest of the heart. However, the SAN is more than a simple clock; it is a clock that adjusts its pace according to the metabolic requirements of the organism. The Hyperpolarization-activated Cyclic Nucleotide-gated channels (HCN1–4) are the structural component of the funny (If) channels; in the SAN the If current is the main driving electrical force of the diastolic depolarization and the HCN4 is the most abundant isoform. The generation of HCN KO and transgenic mouse models has advanced the understanding of the role of these channels in cardiac excitability. The HCN4 KO models that were first developed allowed either global or cardiac-specific constitutive ablation of HCN4 channels, and resulted in embryonic lethality. A further progress was made with the development of three separate inducible HCN4 KO models; in one model KO was induced globally in the entire organism, in a second, ablation occurred only in HCN4-expressing cells, and finally in a third model KO was confined to cardiac cells. Unexpectedly, the three models yielded different results; similarities and differences among these models will be presented and discussed. The functional effects of HCN2 and HCN3 knockout models and transgenic HCN4 mouse models will also be discussed. In conclusion, HCN KO/transgenic models have allowed to evaluate the functional role of the If currents in intact animals as well as in single SAN cells isolated from the same animals. This opportunity is therefore unique since it allows (1) to verify the contribution of specific HCN isoforms to cardiac activity in intact animals, and (2) to compare these results to those obtained in single cell experiments. These combined studies were not possible prior to the development of KO models. Finally, these models represent critical tools to improve our understanding of the molecular basis of some inheritable arrhythmic human pathologies.